The contribution of social transfers to the reduction of poverty - Nicholas T. Longford; Catia Nicodemo (Institute for the Study of Labor (IZA), 2010)
We interpret social transfers broadly as a set of measures to reduce or relieve poverty, and study how well this purpose is served in the countries that participated in the European Union Statistics on Income and Living Conditions in 2007. Motivated by the findings, we characterise a social transfer system in a country by its potential and effectiveness, and compare the countries for a range of definitions of the poverty threshold. The methods are also applied to two subpopulations of household types.
Keywords: I32; C83; 330; effectiveness of social transfers; equivalized household income; EU-SILC database; potential of social transfers; poverty gap; Sozialtransfer; Sozialpolitik; Armutspolitik; Wirkungsanalyse; Armut; Einkommensverteilung; EU-Staaten